Patient precautions: a forgotten piece of the electronic patient record. - Sands, D. Z. (American Medical Informatics Association, 1995)
We define "patient precautions" as a unique group of data that is an essential component of the electronic patient record. Patient precautions include medication allergies, difficult airway precautions, infection control precautions, and advance directives. Any piece of data that is associated with the patient, can affect the management of his or her care, and is relatively static over time (as compared with the patient's medication list and problem list) can be considered a patient precaution. An important property of precautions is that the relevant aspects may be brought to the user's attention at the time a patient care decision must be made. We believe this class of data elements is a unique and important component of the electronic patient record that makes it more valuable than the paper record.